Unraveling Emotional Intelligence: Exploring Parenting Patterns and Sociodemographic Determinants - Tri Lestari; Nandang Rusmana; Tiane Noor Rahmianti; Ipah Saripah (STAI Hubbulwathan Duri, 2025)
Emotional intelligence (EI) plays a critical role in adolescents' social and academic development. This study investigates the influence of perceived parenting styles and sociodemographic factors on the emotional intelligence of junior high school students. A quantitative descriptive approach was utilized, involving 177 seventh-grade students who completed standardized questionnaires assessing emotional intelligence, parenting styles, and demographic information. Findings reveal that 51% of students exhibit moderate levels of emotional intelligence. The most commonly perceived parenting styles were permissive and indifferent, while students who perceived their parents as authoritative demonstrated higher EI levels. Significant differences in EI were also found across gender, age, and parental education. Female students reported higher EI scores than males. Students aged 13 exhibited greater emotional intelligence compared to those aged 12 and 14, potentially due to key developmental transitions at that age. Furthermore, higher parental education was associated with elevated EI levels among students. These results underscore the relevance of parenting style and sociodemographic background in shaping emotional intelligence during early adolescence. Schools are encouraged to support the development of EI through structured counseling programs. School counselors should tailor interventions based on students’ developmental stages and family contexts. Emotional intelligence among junior high school students is significantly shaped by parenting styles and demographic factors. Future research should explore additional variables such as socioeconomic status and cultural background to inform more comprehensive and culturally responsive interventions.